An Arabic Manuscript on the History of Iṣlāḥ and Irshād ‘Revolution’ in Indonesia - Ahmed Ibrahim Abushouk (Studia Islamika, 2014)
This article deals with an Arabic manuscript written in 1960s by a Ḥaḍramī migrant settled in Indonesia and kept in circulation up to the present time. The purpose of this article is to give a textual analysis of the manuscript and assess its contribution to the history of the Ḥaḍramī migration to the Netherlands East Indies and the Ḥaḍramī awakening that took its shape in the first half of the twentieth century. The manuscript’s contents are systemically assessed and placed in their historical context while being compared with the available primary sources in the field. This content analysis approach enables the author to examine the reliability, objectivity and comprehensiveness of the manuscript in terms of its input to the modern history of the Ḥaḍramī diaspora in Indonesia.DOI: 10.15408/sdi.v21i2.1040